2013
DOI: 10.1093/nar/gkt1100
|View full text |Cite
|
Sign up to set email alerts
|

UniHI 7: an enhanced database for retrieval and interactive analysis of human molecular interaction networks

Abstract: Unified Human Interactome (UniHI) (http://www.unihi.org) is a database for retrieval, analysis and visualization of human molecular interaction networks. Its primary aim is to provide a comprehensive and easy-to-use platform for network-based investigations to a wide community of researchers in biology and medicine. Here, we describe a major update (version 7) of the database previously featured in NAR Database Issue. UniHI 7 currently includes almost 350 000 molecular interactions between genes, proteins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…They also demonstrated ACSS2 is specifically expressed in mouse facial tissue during development. ACSS2 interacts with several genes previously identified by Jugessur et al as genes possibly related to clefting: ALDH1A1, ATIC, CTH, DARS, MTHFD1, CBS, and LPL [Jugessur et al, 2009;Kalathur et al, 2013]. PHYH has been associated with rhizomelic chondrodysplasia punctata, which can include craniofacial anomalies such as micrognathia and high arched palate [Barr et al, 1993;Jansen et al, 1997] PHYH has been shown to interact with PEX7, a previously identified gene possibly linked to clefting [Jugessur et al, 2009;Kalathur et al, 2013].…”
Section: Discussionmentioning
confidence: 97%
“…They also demonstrated ACSS2 is specifically expressed in mouse facial tissue during development. ACSS2 interacts with several genes previously identified by Jugessur et al as genes possibly related to clefting: ALDH1A1, ATIC, CTH, DARS, MTHFD1, CBS, and LPL [Jugessur et al, 2009;Kalathur et al, 2013]. PHYH has been associated with rhizomelic chondrodysplasia punctata, which can include craniofacial anomalies such as micrognathia and high arched palate [Barr et al, 1993;Jansen et al, 1997] PHYH has been shown to interact with PEX7, a previously identified gene possibly linked to clefting [Jugessur et al, 2009;Kalathur et al, 2013].…”
Section: Discussionmentioning
confidence: 97%
“…Besides proteinprotein interactions from 12 different resources (including HPRD, BioGrid, IntAct, DIP, BIND and Reactome databases) as well as four interaction maps produced by computational predictions and two high‐throughput yeast‐2‐hybrid screens, UniHI 7 also comprises curated transcriptional regulatory interactions from three complementary databases TRANSFAC, miRTarBase and HTRIdb. In addition to these interactions, the service also integrated drug target information from DrugBank that can be mapped and visualized online without having to download, manually process and load the data into an external standalone application 68. The data can be filtered by the users (e.g., number of PubMed references, small‐scale or large‐scale experiments, direct or indirect connection, binary or complex interaction).…”
Section: Ppi Studies Combining In Vitro and In Silico Approaches: Fmentioning
confidence: 99%
“…The Hibernate library was employed to handle communications between StemCellNet and the database. Gene annotation was imported from UniHI database (21). Gene and protein identifiers used in the mapping function were uploaded from HGNC and bioDBnet resources (24,34).…”
Section: Methodsmentioning
confidence: 99%
“…To provide a more comprehensive coverage, we therefore also included molecular interactions for both human and mouse, identified in other types of cells. These additional molecular interactions (∼300 000) were imported from different resources (21,22). This expanded dataset enables the user to query interaction data for 36 023 distinct genes or proteins.…”
Section: Data Integrated In Stemcellnetmentioning
confidence: 99%